Position and Functions of Judges in Enforcing the Supreme of the Law: Case Study of Code of Ethics Violation by Judge - Titik Triwulan Tutik (Walisongo Law Review (Walrev), 2021)
This research is a rational-empirical research that aims; First, examine the existence of Judicial Power in a constitutional state based on the 1945 Constitution of the Republic of Indonesia. Second, examine the position of Supreme Court Justices as law enforcement actors in Judicial Power according to the 1945 Constitution of the Republic of Indonesia. Third, analyze whether the function of judges is Agung as a law enforcer in the Judicial Power as regulated in the 1945 Constitution of the Republic of Indonesia reflects the principles of independence. There are two main functions of judicial power as the main characteristics of the rule of law and the principle of the rule of law: First, judicial power, both in terms of substance and administration, has been determined to be independent and integrated under the guidance of the Supreme Court, but at the same time its role The DPR to control the Supreme Court's powers is enhanced through determining the appointment and dismissal of Supreme Court justices, and by establishing a Judicial Commission to oversee the administrative aspects of judicial power. Second, taking into account the considerations of the Supreme Court, the President is given the right to grant clemency, abolition and amnesty. The enforcement of the rule of law is a necessity in a state of law and an independent, neutral (impartial) and competent judiciary is one element. The position and function of the Supreme Court judge holds a very important position and role, in enforcing the rule of law.Â Penelitian ini adalah penelitian rasional-empiris yangÂ  bertujuan; Pertama, mengkaji eksistensi Kekuasaan Kehakiman dalam negara Hukum berdasarkan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Kedua, menelaah kedudukan Hakim Agung sebagai pelaku penegak hukum dalam Kekuasaan Kehakiman menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Ketiga, menganalisis apakah fungsi Hakim Agung sebagai pelaku penegak hukum dalam Kekuasaan Kehakiman sebagaimana diatur dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 mencerminkan prinsip-prinsip independensi. Terdapat dua fungsi utama dari kekuasaan kehakiman sebagai ciri pokok negara hukum dan prinsip negara hukum: Pertama, kekuasaan kehakiman, baik dari segi subtansinya maupun administrasinya, telah ditetapkan bersifat mandiri dan terpadu di bawah pembinaan MA, tetapi pada saat yang bersamaan peran DPR untuk mengontrol kekuasaan MA ditingkatkan melalui penentuan pengangkatan dan pemberhentian hakim agung, dan dengan pembentukan KY untuk mengawasi segi-segi administrasi kekuasaan kehakiman. Kedua, dengan memperhatikan pertimbangan MA Presiden diberi hak untuk memberikan grasi, abolisi dan amnesti. Penegakkan supremasi hukum merupakan sebuah keniscayaan dalam negara hukum dan peradilan yang mandiri (independen), netral (tidak memihak) dan kompeten merupakan salah satu unsur. Kedudukan dan fungsi hakim agung memegang posisi dan peran yang sangat penting, dalam penegakkan sumpremasi hukum tersebut.